THE HUBUNGAN ANTARA INDEKS MASSA TUBUH DAN AKTIVITAS OLAHRAGA TERHADAP FLEKSIBILITAS LUMBAL PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS UDAYANA - I.A Pascha Paramurthi; Nopi Andayani; Susy Purnawati (Majalah Ilmiah Fisioterapi Indonesia, 2015)
This study aims to determine the relation of Body Mass Index (BMI) and sport activities with lumbar flexibility of Students in Medical Faculty Udayana University. This research is a cross-sectional study conducted in May 2014 where the population of this study was students in Medical Faculty Udayana University second semester to eight semester which has fulfilled the inclusion and exclusion criteria. The simple random sampling technique is used to select a sample of college students and obtained 62 samples. The results showed that 62 students aged 18-23 years found 12 people with overweight have limited lumbar flexibility and 16 people student obese, have limited lumbar flexibility. Out of 62 students found 33 people with sports activities lacked have limited lumbar flexibility, and 19 students with good sports activities have good lumbar flexibility. Based on the chi-square test p value = 0.027 (p <0.05), which means there is a significant association between BMI on lumbar flexibility. Then, based on chi-square test showed p = 0.000 (p <0.05), which means there is a significant association between the activity of exercise on lumbar flexibility.